The substantiation of research problem actuality for health safety competence of students-foreigners formation in Ukrainian higher educational establishments - Britan, Y. A. (Problems of Engineer-Pedagogical Education, 2018)
An analyze of problems which come out from participation of students-foreigners into education/bringing-up process of Ukrainian higher educational establishments are contributed at the article. A health as characteristic of quality preparation of students is considered. It is set that providing of health culture and healthy life of future specialist with certain professional activity scientists bind to the process of P.E that it is suggested with various ways and facilities for perfect. It is set that at the modern stage of personality formation including the professional preparation of future specialist taking into account a priority of the competency-based approach for their providing and there is a question about the health safety competence. The lines of problem research for students-foreigners preparation in Ukrainian higher educational establishments are analyzed. It is set that modern scientists bind the problem of foreign students preparation is closely connected with their language preparation at the preparatory courses, with adaptation of foreign students during propaedeutic preparation and trade training. The current rifts which are responsible for problem actuality of healthy life formation, health cultures, health safe competence of students-foreigners and were not taking account at the research article are determinate.